Skills mismatch and wage inequality: evidence for different countries in Europe - Santos, Marcelo; Sequeira, Tiago Neves (Technological and Economic Development of Economy, 2014)
This paper studies the relationship between mismatch between workers’ skills and labour market requirements throughout different European Countries. It reports evidence that in several countries, over-skilled people tend to have a wage penalty and under-skilled people tend to have a premium. Interestingly, despite the typical effects of education, tenure, experience, and gender in wages being very similar, the effects of mismatch between skills and labour market requirements differ considerably across the wage distribution and the European Countries.